The Implementation of an Artificial Intelligence-Based Virtual Assistant Chatbot for Academic Information Services - Toriq Alfan Yasir; Baiq Andriska Candra Permana -; Aris Sudianto (Universitas Wahid Hasyim, 2026)
The academic information services at the Faculty of Engineering, Hamzanwadi University currently still rely on manual methods that require considerable time and effort, especially in answering repetitive questions. Therefore, this study proposes the use of an artificial intelligence-based chatbot to provide academic information automatically through the WhatsApp platform. This chatbot system is built using the n8n platform for workflow automation and Gemini AI for natural language processing (NLP), enabling it to understand and provide relevant answers to students' questions. In this study, the system was tested through a series of trials to evaluate the effectiveness of the chatbot in delivering academic information services, such as academic schedules, course registration (KRS), and other related information. The results showed that the implementation of this chatbot can improve the efficiency of academic services by providing fast and accurate responses, as well as reducing the workload of administrative staff.